Taxonomic revision of the ciliate genus Zosterodasys Deroux, 1978 (Protista: Ciliophora: Synhymeniida) - Vďačný, Peter; Tirjaková, Eva (Zootaxa, 2012)
The ciliate genus Zosterodasys was established with Z. agamalievi as the type species by Deroux (1978). Zosterodasys ischaracterized by (i) an obovoidal to ellipsoidal body which is not differentiated into a rostrum anteriorly; (ii) a conspicuouscyrtos, i.e., an obconical cytopharyngeal apparatus; and (iii) a special thickly ciliated structure, the so-called synhymenium,extending obliquely from the left to the right dorsal cell surface across the ventral side and thus interrupting all ventral ciliaryrows and some dorsal ones. Altogether 31 nominal species were originally described or subsequently combined withZosterodasys. However, we recognize only nine of them as reliable Zosterodasys species, eleven represent nomenclaturalsynonyms, one is a junior primary homonym, five are classified as species inquirendae, and five belong to other genera. Weprovide the following data for each reliable Zosterodasys species: author, date, and journal page of the original description; listof synonyms; diagnosis; type locality; type material; etymology; and remarks. Based on the morphologic and morphometriccharacters, we prepared an illustrated taxonomic key, containing all Zosterodasys species considered identifiable in this revision. Further, we discuss characters that have been used in the morphological taxonomy of the genus Zosterodasys.